Celtic Provenance in Traditional Herbal Medicine of Medieval Wales and Classical Antiquity - Wagner, Charles; De Gezelle, Jillian; Komarnytsky, Slavko (Frontiers in Pharmacology, 2020)
Abstract The Celtic linguistic community dominated large spans of Central and Western Europe between 800 BC and 500 AD, but knowledge of their traditional medicine is very limited. Multiple progressive plant gains in Neolithic settlements along the Danube and up the Rhine valleys suggested that taxon diversity of gathered plants peaked at the Balkans and was subsequently reduced as crop and gathered plants packages were adopted and dispersed throughout Neolithic Europe. This process coincided with the Bronze Age migration of the R1b proto-Celtic tribes, and their herbal traditions were occasionally recorded in the classic Greco-Roman texts on herbal medicines. The provenance of Celtic (Gallic) healing methods and magical formulas as recorded by Pliny, Scribonius Largus, and Marcellus Empiricus can still be found in the first part of the medieval Welsh (Cymry) herbal manuscript Meddygion Myddfai (recipes 1-188). Although the majority of Myddfai I recipes were based on the Mediterranean herbal tradition of Dioscorides and Macer Floridus, they preserved the unique herbal preparation signatures distinct from continental and Anglo-Saxon counterparts in increased use of whey and ashes as vehicles for formulation of herbal remedies. Six plants could be hypothetically attributed to the Celtic (Welsh) herbal tradition including foxglove (Digitalis purpurea L.), corn bellflower (Legousia speculum-veneris L.), self-heal (Prunella vulgaris L.), sharp dock (Rumex conglomeratus Murray), water pimpernel (Samolus valerandi L.) and river startip (Scapania undulata L.) This review provides initial evidence for traces of Celtic framework in the Welsh herbal tradition and warrants further investigations of bioactivity and clinical applications of the described plant leads.